2015
DOI: 10.1016/j.jvs.2014.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and respiratory-induced deformation of abdominal branch vessels and stents after complex endovascular aneurysm repair

Abstract: Sn-renals were angled more inferiorly at the branch and more angulated at the stent end than F-renals due to stent placement strategies. Sn-LRAs exhibited a significant change in end-stent angle and curvature during respiration, a finding that may compromise long-term durability for parallel stent graft configurations. Further investigation is warranted to better optimize anatomic, patient, and branch vessel stent selection between fenestrated and snorkel strategies and their relationship to long-term patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…17,18 This acute angulation may precipitate material fatigue more rapidly using currently available mating stents. The respiratory motion experienced by the renal arteries is great 10,11 and the vessels themselves are smaller than visceral arteries (4e5 mm), which may place more stress on a mating stent. As well, there is a higher resistance perfusing an end organ, as opposed to the low resistance systems of the mesenteric and hepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 This acute angulation may precipitate material fatigue more rapidly using currently available mating stents. The respiratory motion experienced by the renal arteries is great 10,11 and the vessels themselves are smaller than visceral arteries (4e5 mm), which may place more stress on a mating stent. As well, there is a higher resistance perfusing an end organ, as opposed to the low resistance systems of the mesenteric and hepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…9 The motion imposed on the stent once in vivo may also play a role on the durability. 10,11 Mating stent choice for branched endografts has been a controversial topic among users of the technology since its inception. Proponents of self-expandable stents cite their flexibility and conformability as the rationale for superiority over balloon expandable stent grafts, while those who favour balloon expandable stent grafts cite their smaller delivery system and precise deployment as beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…There are scan data in the literature evaluating branch morphology related to endovascular repair of complex aortic aneurysms. Ullery et al 11 reported on geometry and respiratory-induced deformation of branch vessels after complex endovascular aneurysm repair, comparing morphology of branches arising from snorkels and fenestrations. Those branches arising from snorkels, in particular the renal arteries, had significant change in end-stent angle and curvature, especially during respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Stented visceral arteries exhibit negligible branch angulation due to the mechanical support of stents, but experienced significant deformation distal to the stents [27]. …”
Section: Discussionmentioning
confidence: 99%